Atividade fungicida de triazóis obtidos a partir de glicerol sobre colletotrichum gloeosporioides - Gomes, Ediellen Mayara Corrêa (2014)
Anthracnose is responsible for significant damage in the post-harvest fruit papaya, causing significant economic losses to producers. So, it was evaluated the efficiency of new molecules triazole fungicides group derived from glycerol on in vitro handling